DO OCCUPATIONAL HAZARDS AFFECT REVENUE EARNINGS OF CASSAVA PROCESSORS IN RIVERS STATE, NIGERIA? Introduction, Methodology, Results and Discussion, Conclusion and References - Ndubueze-Ogaraku, Mercy Ebere; Ezeala, Obinna Darlington; Omasanuwa, Zelda Anne (Advances in Social Sciences Research Journal, 2020)
Farming and food processing have been described as one of the most hazardous activities especially in developing countries. The associated hazards have the potential to affect revenue earned by the workers in the agriculture sector. The study was aimed at investigating whether occupational hazards affect revenue earned by cassava processors in Rivers State, Nigeria. Specifically processing activities, occupational hazards and safety measures adopted by the processors were identified. Effects of occupational hazards on revenue earnings of the cassava processors were determined. 25 respondents were randomly selected from four communities in Obio/Akpor and Etche Local Government Areas making a total of 100 respondents. Data were collected with the use of questionnaire administered to the 100 respondents. Results of the study showed that women dominated cassava processing enterprise with the mean age of 43 years. The majority (37.4%) processed cassava into garri while 32 per cent processed cassava into garri and fufu products. Inhalation of smoke ranked highest among the occupational hazard identified. The regression analysis result showed that cost of cassava, the quantity of cassava tuber and quantity of fufu had a positive influence on revenue earned by the processors at 1% significant level each. However, the quantity of garri produced showed a negative relationship with the revenue earned by the processors at 1% significant level. Occupational hazard did not show a significant effect on the amount of revenue earned by cassava processors. It is recommended that management should re-enforce the use of personal protective equipment by all workers to reduce occupational risks and hazards in cassava processing firms.